2014
DOI: 10.1080/09535314.2014.939949
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Gtap-Mrio and Wiod Databases for Carbon Footprint Analysis

Abstract: In this paper we explore the use of two different global multiregional input-output databases (GTAP-MRIO and WIOD) for the calculation of the global carbon emissions embodied in the final demand of nations (carbon footprint). We start our analysis with a description of the main characteristics of the databases and comparing their main components. Then, we calculate the carbon footprint with both databases and identify (from a global perspective) the most relevant factors underlying the resulting differences us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 31 publications
0
49
2
Order By: Relevance
“…Although the majority of previous LCSA studies using IO analysis were case studies focusing on sustainability impacts of products or processes in a single country [95], a MRIO analysis is critical for taking into account the role of international trade [96,97]. This is important since the majority of countries are open economies and life-cycle sustainability impacts of products are found in the geographical boundary of multiple countries [98,99].…”
Section: Broadening the Object Of Analysis: Revealing Macro-level Impmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of previous LCSA studies using IO analysis were case studies focusing on sustainability impacts of products or processes in a single country [95], a MRIO analysis is critical for taking into account the role of international trade [96,97]. This is important since the majority of countries are open economies and life-cycle sustainability impacts of products are found in the geographical boundary of multiple countries [98,99].…”
Section: Broadening the Object Of Analysis: Revealing Macro-level Impmentioning
confidence: 99%
“…Overall, the use of MRIO databases might result in significant uncertainties in LCSA results. To minimize such uncertainties, one suggested method is to make comparisons between different MRIO databases [96,150,154]. As an alternative method, the authors suggested an uncertainty analysis of economic input-output relationships and environmental intensity vectors that can improve the validity of the result presented in MRIO studies.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…The factor energy (E) is further split up into 26 types of energy, from which CO 2 e emissions of production are derived, a part of which constitutes the domestic indirect CO 2 e emissions of households. The imported indirect CO 2 e emissions of households are taken from simulation results with a MRIO model (Arto et al, 2014). The labour market is specified via wage curves, where wage increases by industry depend on productivity, the consumer price and the distance to full employment.…”
Section: The Modelmentioning
confidence: 99%
“…Empirical assessments revealed the level of differences in carbon footprints calculated with the various MRIO models (Arto et al, 2014;Inomata and Owen, 2014;Owen et al, 2014aOwen et al, , 2014bWilting, 2012). However, in order to inform policy development, findings derived from different MRIO models should have similar overall messages.…”
Section: Introductionmentioning
confidence: 99%